Quantification of lysosphingomyelin and lysosphingomyelin-509 for the screening of acid sphingomyelinase deficiency - Francyne Kubaski; Alberto Burlina; Danilo Pereira; Camilo Silva; Zackary M. Herbst; Franciele B. Trapp; Kristiane Michelin-Tirelli; Franciele F. Lopes; Maira G. Burin; Ana Carolina Brusius-Facchin; Alice B. O. Netto; Edina Poletto; et al. (Orphanet Journal of Rare Diseases, 2022)
Abstract Background Acid sphingomyelinase deficiency (ASMD) is a lysosomal disorder caused by deficiency of acid sphingomyelinase (ASM) leading to the accumulation of sphingomyelin (SM) in a variety of cell types. Lysosphingomyelin (LysoSM) is the de-acetylated form of SM and it has been shown as a biomarker for ASMD in tissues, plasma, and dried blood spots (DBS) and lysosphingomyelin-509 (LysoSM509) is the carboxylated analogue of LysoSM. High levels of Lysosphingomyelin 509 (LysoSM509) have also been shown in ASMD patients. In this study, we report the utility of the quantification of LysoSM and LysoSM509 in DBS of patients from Latin America with ASMD by ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS). Results DBS samples from 14 ASMD patients were compared with 15 controls, and 44 general newborns. All patients had their diagnosis confirmed by the quantification of ASM and the measurement of the activity of chitotriosidase. All patients had significantly higher levels of lysoSM and lysoSM509 compared to controls and general newborns. Conclusions The quantification of lysosphingolipids in DBS is a valuable tool for the diagnosis of ASMD patients and lysoSM can be useful in the differential diagnosis with NPC. This method is also valuable in the ASMD newborn screening process.